(3cJGH aj GdJaSjQs - (3EHQGgje Hf eMehO Hf CHj GdMSjfs ((3YHO GdYRjR GdedbH HQcf YOd s)
(3ChdgG (B:s
(3Cf CaVd GdYdhe Yde cJGH Gddg GdfGRd ef YfOg s
(3BNQgG (B:s
(3GdNfGS GdTjWGf dCfg jNfS YfO PcQ Gddg JYGdi hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdJaSjQ hYdhe GdbQBfs